The Effect of Nutrition and Drug Interactions (Methylphenidate HCl) on ADHD in a Young Adult: A Case Report - Permatasari, Fitiara Indah; Farapti, Farapti; Jassey, Babucarr; Stephens, Moses Tende; Zean, Gabriel (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: ADHD is a common neurodevelopmental condition often managed with stimulant medications such as methylphenidate. While pharmacotherapy remains effective for symptom controlgrowing attention has focused on the role of nutrition in modulating treatment outcomes and overall management of ADHD. However, concerns remain regarding long-term outcomes, adverse effects, and dependence on medication. In recent years, research has increasingly emphasized a more integrative perspective beyond pharmacotherapy, incorporating environmental and nutritional factors to a more comprehensive understanding, including the role of environmental factors, diet, and nutrition. Methods: This case report discusses a 20-year-old female college student with a history of ADHD who presented with behavioral disturbances and sleep deprivation. She had previously shown improvement in focus and academic performance with methylphenidate (CONCERTA), but experienced weight gain as a side effect, motivating her to study nutritional science. Nutritional factors and food–drug interactions appeared to influence both the expression of ADHD symptoms and the tolerability of pharmacotherapy. Discussion: This case highlights individual variability in response to methylphenidate, particularly concerning metabolic effects. The effectiveness and adverse reactions to ADHD medications may be influenced by dietary interactions, suggesting the importance of a personalized treatment approach. A well-balanced diet may enhance cognitive performance and improve pharmacologic tolerability, especially when it includes adequate intake of protein, unsaturated fats, and essential micronutrients. Conclusion: The management of ADHD should consider both pharmacological and nutritional factors. Integrating dietary support into treatment plans may enhance outcomes and reduce side effects, offering a more holistic and individualized model of care.